Construction on the Degenerate Poly-Frobenius-Euler Polynomials of Complex Variable - Ghulam Muhiuddin; Waseem Ahmad Khan; Deena Al-Kadi (Journal of Function Spaces)
In this paper, we introduce degenerate poly-Frobenius-Euler polynomials and derive some identities of these polynomials. We give some relationships between degenerate poly-Frobenius-Euler polynomials and degenerate Whitney numbers and Stirling numbers of the first kind. Moreover, we define degenerate poly-Frobenius-Euler polynomials of complex variables and then we derive several properties and relations.